Medication Adherence Among Patients With Chronic Hepatitis Receiving Antiviral Treatment. (March 2019) - Go, Hirofumi; Tanaka, Makoto; Yamamoto-Mitani, Noriko; Suzuki, Miho; Kawakami, Aki; Masaki, Naohiko; Shimada, Megumi
Abstract : This study aimed to evaluate medication adherence and associated factors among patients with chronic viral hepatitis. A cross-sectional questionnaire survey was conducted in 171 outpatients receiving antiviral treatment of chronic viral hepatitis at 6 national/regional liver disease treatment centers in Japan. Medication adherence was calculated as the subject-reported number of antiviral tablets taken in the past 2 weeks compared with the prescribed number of tablets. Subjects were divided according to 100% adherence or nonadherence. The impact of items pertaining to everyday experiences and perceptions regarding medication adherence were examined. Factors associated with medication adherence were identified via multiple logistic regression. The mean medication adherence rate was 95.8% ± 9.5% (range = 0%–100%), although a smaller proportion (95 subjects; 55.6%) was 100% adherent. Multiple logistic regression indicated a greater "lack of understanding of need for medication" (1 point: odds ratio (OR) = 1.51, 95% confidence interval (CI) [1.30, 1.76], p ⩽ .01) and greater "restriction in life due to medication" (1 point: OR = 1.26, 95% CI [1.03, 1.54], p = 0.03) as associated with nonadherence. In conclusion, to improve medication adherence, healthcare professionals should improve patients' understanding of the need for medication and minimization of life restrictions.